2018
DOI: 10.1097/bot.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Mortality After Hip Fracture Surgery: The Hip Fracture Estimator of Mortality Amsterdam

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 28 publications
3
44
2
Order By: Relevance
“…Our work confirms the few previous reports that have shown that urea is associated with increased mortality in HF patients [14,18] and numerous studies demonstrating such link in older adults with serious illnesses. Our results, however, are the first to demonstrate in HF patients an association between admission urea and HPIR, indicating that blood nitrogen homeostasis is an important regulator of susceptibility and response to inflammation/infection.…”
Section: Hpir (33)supporting
confidence: 92%
See 2 more Smart Citations
“…Our work confirms the few previous reports that have shown that urea is associated with increased mortality in HF patients [14,18] and numerous studies demonstrating such link in older adults with serious illnesses. Our results, however, are the first to demonstrate in HF patients an association between admission urea and HPIR, indicating that blood nitrogen homeostasis is an important regulator of susceptibility and response to inflammation/infection.…”
Section: Hpir (33)supporting
confidence: 92%
“…Only few studies focussed on urea, and the published data have been conflicting. Elevated urea on admission has been reported as an independent predictor of in-hospital mortality [14] and included in some scoring models [17,18,51], but according to other studies urea was only marginally related [16] or not correlated with fatal short-and long-term outcome [15,52].…”
Section: Hpir (33)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 , and the main characteristics of the included trials were summarized in Table 1 . Fourteen of 18 were prospective cohort studies [ 7 20 ], and four were retrospective cohort studies [ 21 24 ]. These studies enrolling 295,285 subjects were published between 2000 and 2018, with a sample size ranging from 272 to 134,144.…”
Section: Resultsmentioning
confidence: 99%
“…Femoral intertrochanteric fracture and femoral neck fracture are the two main types. Hip fracture is regarded as a result of demographic aging, and age is the major risk factor for mortality in patients with hip fractures [ 4 , 5 ]. Hip fractures can exact a terrible toll on the elderly and lead to severe complications and high mortality due to their severity and high economic cost [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%